Study on Adsorbent Characteristics of Coconut Coir as a Bio Sorbent for Removal of Methylene Blue Dye. Issue 1 (20th October 2021) - Malhotra, Anu; Lokhande, Rama S; Sahu, Rajesh; Jain, Sushil K.; Sharma, K. B.; Tripathi, Balram
Abstract: Adsorption of a cationic dye, like methylene blue (MB) onto coconut coir dust, is investigated. Coconut coir is a by‐product of coconut industries. Increasing concerns about environment, global warming have led the scientists to focus on the use of agricultural residue and plant waste fibers. Due to the presence of hydroxyl and polar groups in various constituents of cellulosic fibers, the moisture sorption is expected quite high. Objective of this study is to investigate the potential of coconut coir as bio sorbent for the removal of cationic dye (methylene blue). Adsorption is studied as a function of concentration of both adsorbate and adsorbent with pH and temperature.